PCSK9i promoting the transformation of AS plaques into a stable plaque by targeting the miR-186-5p/Wipf2 and miR-375-3p/Pdk1/Yap1 in ApoE−/− mice - Zhao, Yanlong; Liu, Ning; Zhang, Jifeng; Zhao, Lei (Frontiers in Medicine, 2024)
Background Atherosclerosis (AS) is a multifaceted disease characterized by disruptions in lipid metabolism, vascular inflammation, and the involvement of diverse cellular constituents. Recent investigations have progressively underscored the role of microRNA (miR) dysregulation in cardiovascular diseases, notably AS. Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) can effectively reduce circulating levels of low-density lipoprotein cholesterol (LDL-C) and lipoprotein (a) [Lp (a)], potentially fostering a more enduring phenotype for AS plaques. However, the underlying mechanisms by which PCSK9i enhances plaque stability remain unclear. In this study, we used microarray and bioinformatics techniques to analyze the regulatory impacts on gene expression pertinent to AS, thereby unveiling potential mechanisms underlying the plaque-stabilizing attributes of PCSK9i. Methods ApoE−/− mice were randomly allocated into control, AS, PCSK9i, and Atorvastatin groups. The AS model was induced through a high-fat diet (HFD), succeeded by interventions: the PCSK9i group was subjected to subcutaneous SBC-115076 injections (8 mg/kg, twice weekly), and the Atorvastatin group received daily oral Atorvastatin (10 mg/kg) while on the HFD. Subsequent to the intervention phase, serum analysis, histological assessment using hematoxylin and eosin (H&E) and Oil Red O staining, microarray-centered miRNA analysis utilizing predictions from TargetScan and miRTarBase, and analyses using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were executed to illuminate potential pathways. Real-time fluorescence quantitative PCR (RT-qPCR) was employed to quantify the expression levels of target genes. Results In comparison to the control group, the AS group displayed a significant elevation in blood lipid levels. Both PCSK9i and Atorvastatin effectively attenuated blood lipid levels, with PCSK9i exhibiting a more pronounced lipid-lowering impact, particularly concerning TG and LDL-C levels. Over the course of AS progression, the expression levels of mmu-miR-134, mmu-miR-141-5p, mmu-miR-17-3p, mmu-miR-195-3p, mmu-miR-210, mmu-miR-33–5p, mmu-miR-410, mmu-miR-411-5p, mmu-miR-499, mmu-miR-672-5p, mmu-miR-675-3p, and mmu-miR-301b underwent dynamic fluctuations. PCSK9i significantly down-regulated the expression of mmu-miR-186-5p, mmu-miR-222, mmu-miR-375-3p, and mmu-miR-494-3p. Further enrichment analysis disclosed that mmu-miR-186-5p, mmu-miR-222, mmu-miR-375-3p, and mmu-miR-494-3p were functionally enriched for cardiovascular smooth muscle cell proliferation, migration, and regulation. RT-qPCR results manifested that, in comparison to the AS group, PCSK9i significantly upregulated the expression of Wipf2, Pdk1, and Yap1 (p < 0.05). Conclusion Aberrant miRNA expression may play a pivotal role in AS progression in murine models of AS. The subcutaneous administration of PCSK9i exerted anti-atherosclerotic effects by targeting the miR-186-5p/Wipf2 and miR-375-3p/Pdk1/Yap1 axes, thereby promoting the transition of AS plaques into a more stable form.